Comparison between VDD and DDD Pacing in Symptomatic Second degree and Complete Heart Block (Iraqi Journal of Medical Sciences, 2020)
Background: VDD pacing provides the physiological benefits of atrioventricular synchronous pacing with the convenience of a single lead system, but is hampered by uncertainty regarding long term atrial sensing and development of sinus node disease. Objective: To evaluate the efficacy and sensitivity of two different types of dual chamber pacemakers: (VDD and DDD pacemakers) by various electrophysiological and operative parameters in an attempt to determine whether VDD pacemakers are a viable alternative to DDD pacemakers in treatment of patients with 2nd and 3rd degree heart block with normal sinus node function. Method: The study was conducted during the period between April 2006 to September 2007 on 48 patients with symptomatic 2nd degree and complete heart block, attending the Cardiac Care Unit in Al-Kadhimia Teaching Hospital. Those patients divided into two groups: VDD group and DDD group; each consisted of 24 patients. The VDD and DDD pacemakers were implanted in the patients and the tests of efficacy and sensitivity were done at implantation and in the follow up periods (2nd day of implantation, 10 days, 1 month, and 3 months after implantation) for both groups. These tests were: Atrial sensitivity, atrial lead impedance, P-wave amplitude, event histogram (% of atrio-ventricular synchronous pacing), duration of implantation, and duration of fluoroscopy. The outcomes of these tests were compared in both groups. Results: Forty eight patients were implanted; half of them received DDD pacemakers, and the other 24 received VDD pacemakers. At the time of implantation and during the 3 moths of follow up, the DDD group showed significant higher efficacy and sensitivity than the VDD group. After implantation; the mean P-wave amplitude, atrial sensing threshold, atrial lead impedance, and % of AV synchrony were 3.42±1.1 mV; 3.46±1.3mV; 568±103.42?; 95%±7% respectively in DDD group, while they were 2.91±1.3 mV; 2.46±1.18mV; 624.2±136.26?; 90%±8% respectively in VDD group. Implant time was significantly reduced in VDD patients (61.82±14.6 min.) compared with DDD group (72.62±10.4 min.) (p
Keywords: DDD pacemaker; VDD pacemaker; AV blocks; AV synchrony and atrial sensitivity threshold